To factor the given expression, we need to find the greatest common factor (GCF) of the terms.
Step 1: Find the GCF
The GCF of 6, 3, and 9 is 3. The GCF of x^5, x^3, and x^2 is x^2. Therefore, the GCF of the expression is 3x^2.
Step 2: Divide each term by the GCF
Dividing each term by 3x^2, we get:
6x^5 / (3x^2) = 2x^(5-2) = 2x^3
3x^3 / (3x^2) = x^(3-2) = x
-9x^2 / (3x^2) = -3
Step 3: Rewrite the expression in factored form
Putting it all together, the expression can be factored as:
3x^2(2x^3 + x - 3)
What is the expression in factored form?
6x^5+3x^3−9x^2
show steps
1 answer